Enhancing absorptive capacity through communication: Mediating role of trust and knowledge sharing. A case of virtual universities - Zia Ur Rehman; Kausar Fiaz Khawaja; Syed Ahmad Ali (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
This study aims to highlight the importance of communication and absorptive capacity in virtual universities of Pakistan. In this relationship, this study also investigates the mediating role of trust and knowledge sharing. This study applies social exchange theory to understand the relationship among variables. Some of the relationship between variables was also supported through theory of knowledge creation. For this study, data was collected from 267 employees of two virtual universities in Pakistan. After running the reliability & validity tests, this study used PROCESS Macros by Hayes for mediation analysis. The results suggest that communication has a positive and significant impact on absorptive capacity. Results further prove that trust and knowledge sharing sequentially mediate the relationship between communication and absorptive capacity. The findings of the study reveal that greater opportunities of communication, trust and knowledge sharing among virtual employees leads to build their absorptive capacity. This study is useful for virtual organizations, as it provides a mechanism of communication to improve the absorptive capacity of cross-functional virtual employees under behavioral stress i.e. trust and knowledge sharing. This study suggests that future research may focus on specific team level analysis for innovative behavior etc.
Keywords: 330; absorptive capacity; trust; knowledge sharing; cross-functional communication; virtual universities